Simultaneous acquisition of functional magnetic resonance images and impedance cardiography. (20th November 2014) - Cieslak, Matthew; Ryan, William S.; Macy, Alan; Kelsey, Robert M.; Cornick, Jessica E.; Verket, Marlo; Blascovich, Jim; Grafton, Scott
Abstract: While simultaneous acquisition of electrocardiography (ECG) data during MRI is a widely used clinical technique, the effects of the MRI environment on impedance cardiography (ICG) data have not been characterized. We collected echo planar MRI scans while simultaneously recording ECG and thoracic impedance using carbon fiber electrodes and customized amplifiers. Here, we show that the key changes in impedance (dZ/dt) and features of the ECG waveforms are not obstructed during MRI. We present a method for ensemble averaging ICG/ECG signals collected during MRI and show that it performs comparably with signals collected outside the MRI environment. These results indicate that ICG can be used during MRI to measure stroke volume, cardiac output, preejection period, and left ventricular ejection time.